Letter from Mary Brown to Jane Tolmach - Mary V. Brown:::::: (1974)
A letter from Mary Brown, the co-chairman for Oxnard Citizens for Responsible Government, to Jane Tolmach discussing the cost of multiple ads that will be run in the Oxnard Press-Courier.